2003
DOI: 10.1007/s00595-002-2563-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Arginase Activity Levels in Patients with Breast Cancer

Abstract: A high arginase level in breast cancer was observed to possibly be released into the serum: namely, the more advanced the breast cancer, the higher the serum level of arginase enzyme activity. Therefore, this enzyme might serve as a useful biological marker in breast cancer while also being an indicator of breast cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…The present results imply that both NOS, which converts arginine to citrulline, and arginase, which converts arginine to ornithine, may be elevated in CS patients. The implication of higher arginase activity in CS is consistent with reports of arginase induction by inflammatory cytokines known to be elevated in cardiac ischemia-reperfusion injury and CS 28 and extends reports of increased arginase activity in a number of disease states, including MI, 29 asthma, 30 breast cancer, 31 and pulmonary hypertension. 22,32 NO also can be produced in large and potentially toxic amounts by iNOS expressed in response to trauma and inflammatory stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…The present results imply that both NOS, which converts arginine to citrulline, and arginase, which converts arginine to ornithine, may be elevated in CS patients. The implication of higher arginase activity in CS is consistent with reports of arginase induction by inflammatory cytokines known to be elevated in cardiac ischemia-reperfusion injury and CS 28 and extends reports of increased arginase activity in a number of disease states, including MI, 29 asthma, 30 breast cancer, 31 and pulmonary hypertension. 22,32 NO also can be produced in large and potentially toxic amounts by iNOS expressed in response to trauma and inflammatory stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…While playing roles in amino acid metabolism, increased ARG1 expression is reported in patients with advanced cancer, including hepatocellular carcinoma, renal cell carcinoma and breast cancer (77)(78)(79)(80)(81). A study in preclinical murine models has also shown that inhibition of ARG1 in the skin is associated with increased inflammation and defects in matrix deposition (82).…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative arginine-enriched nutrition significantly improved the long-term overall survival and long-term disease-specific survival in malnourished patients with head and neck cancer (Buijs et al, 2010). Higher expression and activity of ARG1 are often observed in the blood of cancer patients (Polat et al, 2003;Grabon et al, 2009;Rodriguez et al, 2009). After surgical removal of malignant tumors, remnant cells can proliferate.…”
Section: Discussionmentioning
confidence: 99%